New approach for layer thickness measurements of coatings using pulsed lock-in thermography. Issue 2 (15th March 2022) - Hoffmann, D.; Bastian, M.; Schober, G.
ABSTRACT: The coating of materials has grown to an important treatment for improving functionality and appearance of components. A decisive factor for a reliable and consistent performance in its field of application is the layer thickness of coated materials. Consequently, monitoring and controlling the thickness, especially the homogeneity of the coating, represent relevant tasks on a large scope. Active thermography has been established as a method for quality monitoring, but excitation sources for conventional lock-in thermography are either very expensive or relatively inert. Commonly used excitation sources for pulse thermography have a high responsiveness, but a lower signal-to-noise-ratio (SNR) usually confines the result. In this paper, a novel approach is presented where the sample is periodically excited with consecutive pulses and submitted to a lock-in evaluation. This so-called pulsed lock-in thermography offers a less expensive and reproducible way for non-destructive testing and has the potential for large-area measurement of the thickness of coatings.